2008
DOI: 10.1007/s12156-008-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of salivary gland malignancies: current and developing therapies

Abstract: Salivary gland tumors are rare, clinically diverse neoplasms that represent less than 1% of all malignancies. In locoregional recurrent or metastatic disease, systemic therapy is the standard approach. While numerous small phase II studies have evaluated the activity of cytotoxic agents, either alone or in combination, the response rates are generally modest with objective response rates ranging from 15%-50%. Duration of response is cited in the range of 6-9 months. Given this, further evaluation of novel ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…However, if we look at each salivary gland in turn, several large series have shown that mucoepidermoid carcinoma is only the commonest cancer in the parotid glands, comprising around 33% [14, 15]. Adenoid cystic carcinoma is the commonest cancer in the submandibular and minor salivary glands, making up 42–49% [14, 15]. A review of 45 parotid cancer patients treated at the author's institute from 2000 to 2010 also shows mucoepidermoid carcinoma to be the commonest type (Table 1).…”
Section: Histologymentioning
confidence: 99%
“…However, if we look at each salivary gland in turn, several large series have shown that mucoepidermoid carcinoma is only the commonest cancer in the parotid glands, comprising around 33% [14, 15]. Adenoid cystic carcinoma is the commonest cancer in the submandibular and minor salivary glands, making up 42–49% [14, 15]. A review of 45 parotid cancer patients treated at the author's institute from 2000 to 2010 also shows mucoepidermoid carcinoma to be the commonest type (Table 1).…”
Section: Histologymentioning
confidence: 99%
“…Acinic cell carcinoma is also considered to be a low-grade tumour which seldom invades the facial nerve. Regional recurrences occur late in this tumour but 16-20% of patients eventually die of this cancer [14].…”
Section: Histologymentioning
confidence: 99%
“…However, if we look at each salivary gland in turn, several large series have shown that mucoepidermoid carcinoma is only the commonest cancer in the parotid glands, comprising around 33% [14,15]. Adenoid cystic carcinoma is the commonest cancer in the submandibular and minor salivary glands, making up 42-49% [14,15].…”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations